1997
DOI: 10.1007/s11661-997-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of copper and aluminum alloy 3003 heavily worked by equal channel angular extrusion

Abstract: A technique invented in the former Soviet Union and recently introduced in the United States, called equal channel angular extrusion (ECAE), produces intense and uniform deformation by simple shear and is applied to 25 ϫ 25 ϫ 152-mm billets of Cu 101 and Al 3003. Microcrystalline structures with a grain size of 0.2 to 0.4 m are created during room-temperature multipass ECAE deformation for true strains lying in the range ε ϭ 2.31 to 9.24. Evidence shows that intense simple shear deformation promotes dynamic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(119 citation statements)
references
References 22 publications
4
111
2
2
Order By: Relevance
“…The grain size distribution usually follows a lognormal statistical function [24]. ECAP, especially route B C , in which the work-piece is rotated 90° clockwise between adjacent passes, can produce equiaxed grains (see Fig.…”
Section: Nanostructuresmentioning
confidence: 99%
“…The grain size distribution usually follows a lognormal statistical function [24]. ECAP, especially route B C , in which the work-piece is rotated 90° clockwise between adjacent passes, can produce equiaxed grains (see Fig.…”
Section: Nanostructuresmentioning
confidence: 99%
“…It has been shown that four or more passes creates a homogeneous and stable microstructure. 2 In addition, by choosing appropriate billet orientations as it enters the extrusion die on each pass, a variety of microstructures and textures can be developed. ECAE, therefore, has a potential to emerge as an important metal processing method for obtaining ultra-fine grain structures in alloys in bulk forms.…”
Section: Description Of Ecaementioning
confidence: 99%
“…Spot welding electrodes perform three purposes: (1) to conduct welding current to the work and determine current density in the weld zone, (2) to transmit force to the workpiece, and (3) to dissipate heat from the weld thus thermally constraining the nugget. If the application of pressure were not involved, electrodes could be selected almost entirely on the basis of electrical and thermal conductivity.…”
Section: Upper Electrodementioning
confidence: 99%
“…In many early publications, microstructures produced by ECAE have been described as homogeneous [1,2]. More detailed microstructure analysis however indicates that the ECAEdeformed materials are typically heterogeneous.…”
Section: Introductionmentioning
confidence: 99%